D-2-hydroxyglutarate supports a tolerogenic phenotype with lowered major histocompatibility class II expression in non-malignant dendritic cells and acute myeloid leukemia cells - Hammon, Kathrin; Renner, Kathrin; Althammer, Michael; Voll, Florian; Babl, Nathalie; Decking, Sonja-Maria; Siska, Peter J.; Matos, Carina; Conejo, Zugey Elizabeth Cárdenas; Mendes, Karina; Einwag, Friederike; Siegmund, Heiko; et al. (Haematologica, 2024)
D-2-hydroxyglutarate (D-2-HG) accumulates in patients with acute myeloid leukemia (AML) with mutated isocitrate dehydrogenase (IDH) and in other malignancies. D-2-HG suppresses antitumor T-cell immunity but little is known about potential effects on non-malignant myeloid cells. Here we show that D-2-HG impairs human but not murine dendritic cell differentiation, resulting in a tolerogenic phenotype with low major histocompatibility class II expression. In line with this, IDH-mutated AML blasts exhibited lower expression of HLA-DP and were less susceptible to lysis by HLA-DP-specific T cells. Interestingly, besides its expected impact on DNA demethylation, D-2-HG reprogrammed metabolism towards increased lactate production in dendritic cells and AML. Vitamin C accelerated DNA demethylation, but only the combination of vitamin C and glycolytic inhibition lowered lactate levels and supported major histocompatibility complex class II expression. Our results indicate an unexpected link between the immunosuppressive metabolites 2-HG and lactic acid and suggest a potentially novel therapeutic strategy with combinations of anti-glycolytic drugs and epigenetic modulators (hypomethylating agents) or other therapeutics for the treatment of AML.
Gesehen am 03.04.2025